2023
DOI: 10.1039/d2se01683d
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow hydrogenolysis of 5-hydroxymethylfurfural into 2,5-dimethylfuran over alumina-supported nickel–iron alloy catalysts

Abstract: Catalytic transformation of furan derivatives to the next generation of biofuel in a continuous operation is a promising platform for an application of sustainable biorefinery. In this study, the as-synthesized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 55 publications
(110 reference statements)
4
21
0
Order By: Relevance
“…The desorption peaks related to the amount and strength of acidity could be categorized into weak (~50-300 °C) and strong (~300-425 °C) acid sites in accordance with former explanation. [5] The peak intensity of NH 3 desorption for the reduced CoAl catalyst was lowest for both weak and strong acid sites; while, the highest acid sited observed by comparing peak intensity was obvious for the reduced PtAl catalyst. It should be noted that the PtAl catalyst did not clearly exhibit the strong acid sites at high temperature ranges of ~300-425 °C.…”
Section: H 2 -Tpr and Nh 3 -Tpd Experimentsmentioning
confidence: 84%
See 1 more Smart Citation
“…The desorption peaks related to the amount and strength of acidity could be categorized into weak (~50-300 °C) and strong (~300-425 °C) acid sites in accordance with former explanation. [5] The peak intensity of NH 3 desorption for the reduced CoAl catalyst was lowest for both weak and strong acid sites; while, the highest acid sited observed by comparing peak intensity was obvious for the reduced PtAl catalyst. It should be noted that the PtAl catalyst did not clearly exhibit the strong acid sites at high temperature ranges of ~300-425 °C.…”
Section: H 2 -Tpr and Nh 3 -Tpd Experimentsmentioning
confidence: 84%
“…It was previously reported that the sites of acidity have significantly an influence on the selective hydrogenation and hydrogenolysis processes in the HMF hydro-conversion. [5,10,18,48] Consequently, the observing acidity by NH 3 -TPD experiments was conducted for all the reduced catalysts and profiles are established in Figure 1b. It was found that the desorption profiles for all the reduced catalysts exhibit two major broad peaks with different levels of the NH 3 desorption capacity.…”
Section: H 2 -Tpr and Nh 3 -Tpd Experimentsmentioning
confidence: 99%
“…The structural analysis by the XRD, XANES, and XPS experiments confirmed the formation of metallic Ni and Re with a minor fraction of NiO and ReO x oxides after reduction process. The coexistence between the metal and metal oxides was advantageous for the hydrogenolysis and hydrodeoxygenation processes [17a,24d] . The hydrogen molecules could dissociate into hydrogen atoms on the active Ni and Re sites; whereas, the carboxyl group could adsorb on the oxophilic sites of NiO and ReO x species.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15] For example, 2,5-furan diformaldehyde, 2,5-furan diformic acid and levulinic acid can be synthesized by the oxi-dation of HMF, and 2,5-dihydroxymethylfuran (DHMF), 2,5-dimethylfuran (2,5-DMF) and 5-methyl-2-furan carbinol (MFA) can be obtained by selective hydrogenation. [16][17][18][19][20][21][22] However, this also poses challenges to for preparing a single product with high selectivity.…”
Section: Introductionmentioning
confidence: 99%